A provision framework and data logging tool to aid the prescription of electronic assistive technology. - Hawley MS; O'Neill P; Webb LH; Roast C (Technology & Disability, 2002)
The provision of complex electronic assistive technology systems for people with severe physical disabilities requires a structured process of assessment, prescription and follow-up. The provision framework developed in Barnsley includes a long-term iterative process of continuing follow-up and optimisation of the prescribed system. A computer-based integrated assistive system has been developed, which includes a software tool to log usage. The expectation is that the information available from data logging will supplement information from communication with the users and carers, and observational data, to give feedback on the success of the prescription that is more objective, comprehensive and easy to collect. Approaches to analysis of the logged data are presented and illustrated by a case study. The results demonstrate that, when usage data are logged within an integrated assistive system, the data can be analysed and presented to give meaningful feedback on the fit of the system to user requirements.